2021
DOI: 10.1186/s40900-021-00296-9
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualising and constructing ‘diversity’ through experiences of public and patient involvement in health research

Abstract: Background Increasing the accessibility of public and patient involvement (PPI) in health research for people from diverse backgrounds is important for ensuring all voices are heard and represented. Critiques of PPI being dominated by ‘the usual suspects’ reflect concerns over the barriers to involvement in PPI faced by people from minority groups or non-professional backgrounds. Yet, what has received less attention is how undertaking PPI work might produce diverse experiences, potentially sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 25 publications
1
40
0
Order By: Relevance
“…For example, partnering with diverse community groups to plan and undertake engagement is recommended,11 43 as is ensuring the professionals involved view consumers as equal and possess linguistic and cultural competency 11 43. Two important factors in the diversity literature that are supported by our findings (while not being standalone themes) are the importance of trusting, long-term relationships17 42 and identifying and mitigating power imbalances 11 43…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…For example, partnering with diverse community groups to plan and undertake engagement is recommended,11 43 as is ensuring the professionals involved view consumers as equal and possess linguistic and cultural competency 11 43. Two important factors in the diversity literature that are supported by our findings (while not being standalone themes) are the importance of trusting, long-term relationships17 42 and identifying and mitigating power imbalances 11 43…”
Section: Discussionmentioning
confidence: 65%
“…It may include having multiple consumers as members of the GDG, or involve a parallel process, for example, as participants in focus groups, interviews and workshops 9. However, consumers from diverse backgrounds may face additional barriers to participation, meaning guideline developers may need to adapt their approach and provide additional support 16 17. Despite the need for specific advice, guidance to address equity in guidelines typically includes little practical advice about how to do this 6 8.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there was limited diversity among advisors who contributed to our study. The need to increase diversity among patient and public partners in health research is an established priority (Reynolds et al 2021). To address this, we have increased our reach to include a more diverse group of patient partners in our current work to implement registries.…”
Section: Discussion: Reflection On Strengths and Limitationsmentioning
confidence: 99%
“…Members are already trying to ensure that those who have less ability to engage with research are invited to participate. Strengthening public involvement and engagement 12 is often associated with training and development, particularly for those who are new to research and to framing feedback. Reporting the impact of PPI in research should include how people with highly embedded and relevant experience are identified and supported.…”
mentioning
confidence: 99%